Educational Assistance Activities in Brokoh Village Through Community Service Program - Audiva Syifa; Ali Uyun; Rangga Noor Sabila; Nila Umi; Risqi Fitrianingsih; Tri Wahyu; Dina Fatimah; Zulham Ikramullah; Daud Rismana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Community service in the field of education is one of the main initiatives of UIN Walisongo Semarang's KKN (Real Work College) programme in Brokoh Village, Wonotunggal District, Batang Regency. Community efforts in upholding the Tri Dharma of Higher Education consist of three main elements: education and training, research and development, and community service. Through community service activities in Brokoh Village, there is synergy between university students and the community as a form of knowledge democracy. The method used in the learning assistance programme is to provide exclusive learning process assistance and provide fun learning methods, for example by providing material through singing, games, quizzes and so on. The purpose of this service is to provide an understanding to the surrounding community of the importance of education as an effort to educate the nation's children and increase the interest in learning of students of SDN Brokoh and MI Islamiyah Brokoh with fun teaching. The form of service is carried out through teaching activities at SDN Brokoh, MI Islamiyah Brokoh and socialising Anti Bullying. The results of this service provide an overview of the enthusiasm and enthusiasm of students of SDN Brokoh and Madrasah Ibtidaiyah Brokoh in carrying out teaching and learning activities.